Poda Na Lima: Value of Education and Social Society Order Based on Local Wisdom - Eka Susanti (AL-ISHLAH: Jurnal Pendidikan, 2023)
Poda na lima are five pieces of advice that are firmly held as the foundation of the Angkola-Mandailing community. This advice includes local wisdom that underlies the social order and contains educational value regarding efforts to cleanse the heart, soul, mind, body, and environment. This study aims to analyze the value of education and the community's social structure based on local wisdom. The focus of the local wisdom studied is Poda na Lima in the Angkola-Mandailing community. This research approach uses a qualitative type of literature study method. Sources of data and analysis materials for research studies use scientific literature obtained from credible websites (Sinta, DOAJ, Scient Direct, Routledge/Tandfonline, Scimago JR). The scientific literature in question includes; articles, proceedings, books, and final student assignments (thesis, theses, dissertations) relevant to the research theme. The results of this study indicate that poda na lima has an extension as a philosophy in the life of the Angkola-Mandailing community. This local wisdom contains an educational value (education for children) in social arrangements based on the purity of intention, physical cleanliness, and public order. The five pieces of advice in local wisdom include paias rohamu (heart/soul), Pematangmu (physical), parabitonmu (clothing), bagasmu (house), and pakaranganmu (environment).